Intelligent Detection and Early Warning of Power System Cybersecurity Threats Based on Multi-modal Large Language Models - Xiaomeng, Li; Bingjie, Lin; Huimin, Li (Journal of Cyber Security and Mobility, 2026)
The escalating sophistication of cyber threats against power systems necessitates advanced detection mechanisms. This research presents a multi-modal large language model framework integrating Supervisory Control and Data Acquisition (SCADA) logs, Phasor Measurement Unit (PMU) measurements, network traffic, and grid topology through cross-modal attention. The architecture employs specialized encoders, including Bidirectional Encoder Representations from Transformers (BERT) for text, transformers for time-series, Convolutional Neural Network-Long Short-Term Memory (CNN-LSTM) for traffic, and graph networks for topology. Evaluation on 2 million samples shows the Multi-modal Large Language Model (MM-LLM) achieves 95.4% accuracy, outperforming traditional machine learning including Support Vector Machine with Radial Basis Function kernel (SVM-RBF) at 77.1% and deep learning methods including Long Short-Term Memory (LSTM) at 82.9% and Memory-Augmented Deep Generative Adversarial Network (MAD-GAN) at 86.1%. The framework maintains 94.2% precision, 96.3% recall, 2.7% false positive rate, and 13.2 ms latency. Early warning capability provides 3.2–4.5 minutes lead time before attacks, enabling proactive defense. Ablation studies confirm cross-modal attention contributes 6.7% improvement, while multi-modal fusion elevates performance from 88.7% to 95.7%, demonstrating effectiveness for critical infrastructure protection.